A Low-Complexity Synchronizer for OFDM-UWB-Based Vehicular Communications - Xiuwen Yin; Jianqi Liu; Yongfeng Su; Xiaoming Xiong; Guohua Xiong (IEEE Access, 2017)
The high implementation complexity of multiband orthogonal frequency-division multiplexing (MB-OFDM) ultra-wideband (UWB) technology is the major hurdle for applying it to vehicular communications. This paper presents a comprehensive synchronizer with low complexity and high performance for the MB-OFDM UWB. A low-complex overall architecture is proposed, in which the sub-functions are divided into amplitude-detection-based functions and phase-detection-based functions. All of the amplitude-detection-based functions are implemented based on a simplified cross correlation-based matched filter, and a serial structure-based auto-correlation block is designed exclusively for carrier frequency offset estimation. Several effective methods for the sub-functions are proposed based on the proposed overall architecture. Evaluation results show that the proposed synchronizer has high performance with low complexity.